(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
An important shallow marine deposit is described and illustrated with focus on the systematics and biostratigraphy of larger foraminifera from three stratigraphic sections of the Becirman Formation from the Batman and Siirt regions (Southeastern Turkey). A quite diverse association, mostly dominated by rotaliids (11 species belonging to 7 genera) and subordinate porcelaneous and agglutinated taxa, is documented as well. The fossil assemblage, including Elazigina dienii, Rotospirella conica, Praelockhartia cf. neoakbari, Cuvillierina cf. sireli associated with Mardinella daviesi and Idalina sinjarica, indicates the late Danian SBZ2. The abundance of rotaliids is linked, in this time frame, to the recovery of the shallow benthic communities after the K/Pg extinction including increase of surface water temperatures and oligotrophy. This was possibly due to the climatic warming recorded at the end of the Danian (Latest Danian Event), thus promoting a rapid adaptative radiation of rotaliids at genus rank.